Universal material template for heterogeneous objects with applications to additive manufacturing. (December 2020) - Tang, Yunlong; Xiong, Yi; Park, Sang-in; Rosen, David W.
Abstract: Additive manufacturing processes enable the fabrication of the material with multiscale complexities. However, to efficiently model the material compositions and microstructures on multiple design scales is an issue for most existing heterogeneous object modeling methods. To solve this problem, a universal material template and its associated heterogeneous object model are developed in this paper. The developed material template aims to provide a standardized description of the material's microstructures. The material descriptors defined in the material template can be used in the developed heterogeneous object model to describe the spatially varied material compositions and microstructures on multiple design scales. In addition to that, a multiscale rendering method is also developed in this paper which can reconstruct the microstructure of multiscale materials defined in the material template. Both mesh and voxel models can be generated by the developed rendering technique for visualization and fabrication purposes. To further validate the effectiveness of the proposed template and rendering methods, the microstructures of three different types of commonly used materials in additive manufacturing processes are reconstructed from the pre-defined material templates. A heterogeneous object model with functional graded multiscale materials is also successfully generated and fabricated by an existing commercial additive manufacturing process. In general, the developed material template and its associated modeling and rendering methods provide the foundation for the multiscale design and modeling of parts fabricated by the additive manufacturing process. Highlights: Both material compositions and microstructures can be quantitatively defined. Both periodic and stochastic microstructures can be described in a universal format. The developed template can be used to model multiscale heterogeneous objects. Rendering algorithm is developed to generate voxel models for AM fabrication.